Reproductive Health Issues - Odinakhan Rakhmanovna Parpieva; Odinakhan Odilovna Djalalidinova (Zien Journals, 2022)
This article contains information on reproductive health, reproductive problems, the Law "On the protection of the reproductive health of citizens", signed by the President of the Republic of Uzbekistan on March 7, 2021, infertility, reproductive technologies, reproductive health protection
Keywords: reproductive health; infertility; reproductive technologies; assisted reproductive technologies